The effect of using animation in the treatment of dyslexia among third- grade primary school students in Jeddah - Al- Tuwairqi, Reem Abdullah (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to measure the effectiveness of animation in the treatment of dyslexia (dyslexia) in the students of learning disabilities in the third grade in Jeddah, Where the semi- experimental curriculum was used on one group that was intentionally chosen from elementary school 194, which consisted of (seven students who suffer from dyslexia and suffer from learning difficulties at the same time. The study was applied in the second semester of the academic year 1437- 1438 AH, and by using a performance test and a notecard to measure the performance aspect of reading skill after its adaptation. The study concluded that there are differences between the average scores of female students of the experimental group in the post- application for performance testing, the card for reading skills and proficiency level (80%) in favor of post- implementation. Based on these results, a number of recommendations and suggestions were presented, including the need to use animation to develop different skills and take advantage of their capabilities in presenting the academic courses.